IPO : a global guide - Espinasse, Philippe (HKU Press, 2014)
In this practical guide to initial public offerings, Philippe Espinasse explains the pros and cons of turning private businesses into listed companies. In straightforward, jargon-free language he details the strategies, procedures, and documentation for different forms of listings, and describes the process of marketing and pricing an international IPO. The guide includes many real-life case studies, sample documents, an extensive glossary of terms, and a review of listing requirements for major stock exchanges. It also discusses recent developments in global equity capital markets. This fully.